Development of fish finding sonar - Ushetti, Ushettige D.J.P.; Somrak Petchartee; Attaphongse Taparugssanagorn; Mongkol Ekpanyapong (Pathum Thani : Asian Institute of Technology, 2017)
In this project, development of fish finding sonar using a Field Programmable Gate Array (FPGA) has been examined. Designing a transmitter circuit and receiver circuit and design a sonar sensor module and ensure it is waterproof has been discussed. Various methods were tried and tested in order to make a better transmitting and receiving circuits with better amplification. In order to get a proper signal from the speaker and to make it properly waterproof, several methods were tried and tested. By using those hardware parts, a fish was detected and the distance to the fish displayed.
A capstone project report submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering Electronics Engineering, School of Engineering and Technology
Capstone Project (B.Sc.)-Asian Institute of Technology, 2017
Keywords: Sonar in fishing; Field programmable gate arrays -- Programming